POTENTIAL MARKET OF FREIGHT EXPRESS USING HIGH SPEED RAILWAY IN JAVA ISLAND - Yudho Nugroho, Ibnu
The development of express transportation in Indonesia currently continues to increase due to the impact of technological developments and digitalization that increase online shopping and e-commerce trends. In the future, freight transportation will be located in four dimensions, namely large volumes of transportation, timely delivery, economical costs, and reducing the impact on the environment. The increasing number of express delivery of goods due to the development of information and communication technology opens up opportunities for high-speed railways to be used as a mode of freight express transportation in the future. High-speed railways have advantages in terms of travel time, with the speed of the Jakarta-Bandung high-speed train reaching 350 km/hour. The faster the travel time can create a faster operational service for shipping freight express, such as the sameday service. With a large transport volume, high-speed railways have the potential for fast delivery times and are environmentally friendly. By using the Stated Preference (SP) method, an experimental design was carried out to create alternative hypotheses for the situation of express delivery services (hypothetical situation) using high-speed railways as freight transport based on the variable difference in rates and delivery times between high-speed railways and trucks. The results of the analysis state that the probability of the Jakarta - Surabaya express delivery of respondents choosing the express mode of transportation using the high-speed railways is 55%. As for Jakarta - Bandung by 22%, so that for long-distance delivery Jakarta - Surabaya using high-speed railways still has the potential to be developed as a mode of freight express transportation. Based on the results of interview surveis high-speed railways have excellent potential in terms of speed, besides that, proper operation management is needed to improve high-speed railways services as freight transport: 1) facilities and infrastructure 2) Rail Freight Masterplan 3) Layout of freight express terminals at high-speed rail stations. 4) Freight express service scheme by high-speed railways. 5) Availability of transshipment technology.